Superconducting Parameters and Size Effects of Aluminum Films and Foils - Maloney, M.D.; de la Cruz, F.; Cardona, M. (American Physical Society, 1972)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Brown University; Estados Unidos